Customer experience in B2B Saas business - Bene, Mónika (2020)
Customer experience has become one of the focus areas of both marketing practice and theory in the recent few years. While the amount of customer touchpoints and channels has increased, companies have less power than ever to control the entire experience. Customer experience management now requires involvement of more business functions from the service provider side than ever before (Edelman & Singer, 2015, Lemon & Verhoef, 2016). Furthermore, customers have become active agents co-creating their experiences together with the company (Prahalad & Ramaswamy, 2004). The main objective of this study is to explore employees’ role and other key influencing factors inside the organization in creating customer experience. This study is centered around customer experience and investigates how customer relationship management and service quality have an impact on it through a case study of a SaaS company. Methodology used for the case study was in-depth interviews with eight employees of the case company. Based on the study findings, it can be implied that the base for providing good customer experience is consistent communication across all customer journey touchpoints within the organisation. In SaaS business, service quality has a significant influence on customer experience. Instrumental performance is the primary source of customer value, hence if the software works reliably, securely and is able to satisfy the business need, customers more willingly continue using it. Expressive performance can provide customer delight, something additional value to the customers as long as the software is viable, reliable and secure in the first place. Furthermore, as customer knowledge is one of the company’s most valuable asset (Crié & Micheaux, 2006), a well-maintained CRM system has a key role in providing customer experience. Employees consider it as an indispensable source of information for efficiently handling customers. Study results show that companies can improve their customer experience by ensuring that customer-specific information is transparent throughout all the touchpoints, by making internal communication more efficient and by focusing on employee training. Besides, process automation and customer-side self-service functionalities have gradually became more important parts of user experience.